1990
DOI: 10.1007/bf00182650
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of idiopathic aseptic necrosis in medically treated alcoholics

Abstract: The occurrence of idopathic aseptic necrosis of bone in multiple sites has been studied in persons who have had medical treatment for excessive consumption of alcohol. The incidence was 5.3% in 1157 such persons and there were 92 different sites in 62 patients. There were 82 lesions affecting the femoral head, 46 in the left hip and 36 in the right. In 10, it was present in the head of the humerus. Multiple foci were found in 6.1% of patients with the disease. In 2 men and 2 women both femoral heads and both h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…ON, especially of the femoral head, in association with chronic alcoholism is fairly common. The incidence rate among alcoholics may not be as high as expected with the incidence of 5.3% in medically treated alcoholics (28,29). Radiographic and pathologic characteristics of ON in patients with aplastic anemia are not unique, being evident in cases of bony necrosis due to other causes.…”
Section: Discussionmentioning
confidence: 88%
“…ON, especially of the femoral head, in association with chronic alcoholism is fairly common. The incidence rate among alcoholics may not be as high as expected with the incidence of 5.3% in medically treated alcoholics (28,29). Radiographic and pathologic characteristics of ON in patients with aplastic anemia are not unique, being evident in cases of bony necrosis due to other causes.…”
Section: Discussionmentioning
confidence: 88%
“…The incidence of ON in persons who have had medical treatment for excessive consumption of alcohol was reported to be 5.3 % (62/1157) by Orlic et al [13]. They found that patients with alcohol-associated ON had femoral head involvement in 89.1 % and multiple foci in 6.1 %.…”
Section: Alcoholmentioning
confidence: 99%
“…Chronic alcohol intake is a common cause of ON; however, multifocal ON is relatively rare. In 1990, Orlić et al [8] reported an incidence of ON in 5.3% of alcoholics, with 6.1% of these being multifocal. In our case, the patient consumed up to 200 mL of alcohol per week.…”
Section: Discussionmentioning
confidence: 99%